Phytomicrobiome Coordination Signals Hold Potential for Climate Change-Resilient Agriculture - Lyu, Dongmei; Backer, Rachel; Subramanian, Sowmyalakshmi; Smith, Donald L. (Frontiers in Plant Science, 2020)
A plant growing under natural conditions is always associated with a substantial, diverse and well-orchestrated community of microbes - the phytomicrobiome. The phytomicrobiome genome is larger and more fluid than that of the plant. The microbes of the phytomicrobiome assist the plant in nutrient uptake, pathogen control, stress management and overall growth and development. At least some of this is facilitated by the production of signal compounds, both plant-to-microbe and from the microbes back to the plant. This is best characterized in the legume nitrogen fixing and mycorrhizal symbioses. More recently we have shown that the lipo-chitooligosaccharide (LCO) microbe-to-plant signals present in both of these symbioses also regulate stress responses in a wide range of plant species, and subsequently that a small protein (thuricin 17) produced by a soybean root associated Bacillus thuringiensis species can also act in this capacity. While thuricin 17 is produced chronically LCO signals are only produced in response to a signal from the plant. It may be that many signal compounds will only be discovered with root associated microbes are exposed to appropriate plant-to-microbe signals (positive regulation), and this might only happen under specific conditions, such as abiotic stress. The production of others might only be released when a plant-to-microbe signal is removed (negative regulation). Some specialist phytomicrobiome members could be made into generalists when exposed to signals from the correct plant species. The use of microbe-to-plant signals can enhance crop stress tolerance and could result in more climate change resilient agricultural systems.